The Effect of Credit, Development, and Marketing Strategy on The Performance of Tegalan Batik SMEs in Tegal Regency - Hasan, Nurkholis; Setiawan, Achma Hendra (Jurnal Ilmu Ekonomi Terapan, 2022)
MMEs have an important role in the Indonesian economy. MMEs Batik Tegal is a business that has high cultural value, and according to BPS data from Tegal Regency, it is stated that the Processing Business ranks the highest where Batik products are the first in Tegal Regency. This study aims to examine the effect of credit, coaching and marketing strategies on the performance of Batik Tegalan SMEs in Tegal Regency. This study uses primary data with a questionnaire method. Questionnaires were obtained from 70 respondents who are owners of MMSE Batik Tegalan who use the facilities of Microfinance Institutions and other Financial Institutions, already have a place of business. The analysis method in this study uses multiple linear regression analysis. The result showed significant effects of credit, coaching, and marketing strategy variables on the performance of Batik Tegalan SMEs in Tegal Regency, which can be seen at the significance level value <0,05. The credit variable has a positive effect with a value of 0,378, the coaching variable has a positive effect with a value of 0,202, and the marketing strategy variable also has a positive effect with a value 0f 0,375.